Validation of robust tools to measure sialorrhea in amyotrophic lateral sclerosis: A study in a large French cohort. Issue 4 (1st May 2013) - Abdelnour-Mallet, Maya; Tezenas Du Montcel, Sophie; Cazzolli, Pamela A.; Assouline, Avi; Pointon, Christine; Leveque, Nathalie; Dominique, Henri; Elmazria, Hassan; Rothmayer, Michaela; Lenglet, Timothee; Bruneteau, Gaelle; le Forestier, Nadine; et al.
Abstract: There is an unmet need for validated tools to measure sialorrhea in amyotrophic lateral sclerosis, especially to evaluate treatments. We assessed the inter-/intra-rate reviewer reliability of two scales: the Oral Secretion Scale (OSS), specifically developed for ALS patients, and the Sialorrhea Scoring Scale (SSS), initially developed for Parkinson's disease patients. Sialorrhea was rated in 69 ALS consecutive patients by four evaluators: two neurologists, one nurse and one speech therapist. Inter-rater reliability was evaluated by the light kappa coefficient and intra-rater reliability by the weighted kappa coefficient. We also compared patients' and caregivers' answers. Results demonstrated that the two scales present a high inter-/intra-rater reliability: weighted kappas were 0.85 for both scales and light kappas 0.89 for the OSS and 0.88 for the SSS. Both scales also showed a good intra-profession reliability (OSS kappa = 0.84; SSS kappa = 0.79) and agreement between patients' and caregivers' answers. The SSS showed a higher responsiveness compared to OSS. In conclusion, both Oral Secretion Scale and Sialorrhea Scoring Scale are reliable tools to measure sialorrhea in ALS patients. Because of the wide range of salivation degrees, SSS may be more sensitive as a tool to evaluate treatments in patients with severe hypersialorrhea.